Talent discovery, layoff risk and unemployment insurance - Marco Pagano; Luca Picariello (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
In talent-intensive jobs, workers' quality is revealed by their performance. This enhances productivity and earnings, but also increases layoff risk. Firms cannot insure workers against this risk if they compete fiercely for talent. In this case, the more risk-averse workers will choose less quality-revealing jobs. This lowers expected productivity and salaries. Public unemployment insurance corrects this inefficiency, enhancing employment in talent-sensitive industries, consistently with international evidence. Unemployment insurance dominates legal restrictions on firms' dismissals, which penalize more talent-sensitive firms and thus depress expected productivity. Finally, unemployment insurance fosters education, by encouraging investment in risky human capital that enhances talent discovery.
urn:nbn:de:hebis:30:3-473902
Keywords: D61; D83; I20; J24; J63; J65; 330; talent; learning; layoff risk; unemployment insurance